2017
DOI: 10.1111/wvn.12222
|View full text |Cite
|
Sign up to set email alerts
|

Frailty as a Predictor of Future Fracture in Older Adults: A Systematic Review and Meta‐Analysis

Abstract: Professional nurses caring for frail or prefrail people should actively develop fracture prevention measures to reduce the risk of death caused by fractures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
25
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 26 publications
3
25
0
2
Order By: Relevance
“…Frailty, the state representing a decline in functional reserves, has emerged as a key aspect in research on population ageing. It is used as a health indicator for how well populations are aging and is commonly used in the context of the elderly facing functional disabilities, as many studies have demonstrated that frail individuals are at a high risk of becoming disabled, independent of the presence of co-morbid diseases [ 8 , 9 , 10 , 11 , 12 , 13 ]; thus, frailty has been suggested as a better predictor of health and well-being than the presence or absence of disease and has been used as an indicator of the compression of morbidity to predict the demands on the healthcare system [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Frailty, the state representing a decline in functional reserves, has emerged as a key aspect in research on population ageing. It is used as a health indicator for how well populations are aging and is commonly used in the context of the elderly facing functional disabilities, as many studies have demonstrated that frail individuals are at a high risk of becoming disabled, independent of the presence of co-morbid diseases [ 8 , 9 , 10 , 11 , 12 , 13 ]; thus, frailty has been suggested as a better predictor of health and well-being than the presence or absence of disease and has been used as an indicator of the compression of morbidity to predict the demands on the healthcare system [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…A total of 969 records were identi ed from the six databases, and after removing the duplicates, 686 were screened for eligibility based on title and abstract. Twenty-three full-text articles were then reviewed for relevance, out of which 18 were excluded because aspects similar to, but not de ned explicitly as, frailty were assessed, e.g., gait speed (17,18), sarcopenia (19), different health indicators (20) or geriatric syndromes (21); outcomes other than mortality were examined, e.g., trauma (22), fractures (23,24), falls (25), high blood pressure and cardiovascular outcomes (26) or heart failure (27); study population included were from clinical practice (28), nursing home (29) or critical care (30) but not from a community setting; the study involved interventions, e.g., treatment modalities (31); or the article was a systematic review protocol or an umbrella review which evaluated frailty scales for clinical outcomes from community, residential care and hospital settings (32)(33)(34). This left ve eligible systematic reviews and meta-analyses in the umbrella review ( Fig.…”
Section: Search Resultsmentioning
confidence: 99%
“…A correlation between comorbidity at discharge and poor functional outcomes has been demonstrated (20). Persons with the physical frailty phenotype have an increased risk of fractures in general and poor surgical outcomes (21,22). A rapid screen for the physical phenotype for frailty -the FRAIL scale has been developed (23-27).…”
Section: High Risk Populationsmentioning
confidence: 99%